GAMBAR BERCERITA RAMAH BERKATA Representasi Keteladanan dalam Gambar Bercerita di Dongeng Anak Corona Series - Ari Susanti (Universitas Muhammadiyah Jember, 2021)
Fairy tale is one of the communication media to convey messages through stories so that they are easily understood by children. This research discusses the Dongeng Corona Series 2 by